IMPLEMENTASI METODE EXTREME PROGRAMMING PADA APLIKASI PELAYANAN PUBLIK KEWASPADAAN NASIONAL DAN PENANGANAN KONFLIK KESBANGPOL KOTA MANADO - Kristofel Santa; Rafter Johanes Karouw (LPPM Unbaja, 2025)
The development of information technology has had a significant impact on various aspects of life, including governance and public services. In this digital era, the use of information technology has rapidly increased, enabling the creation of good governance through transparency and accountability. In Manado City, the National Unity and Politics Agency (Kesbangpol) has a mission to provide fast, accurate, and friendly services to the community. However, limitations in human resources and manual archiving sistems have led to delays in issuing activity recommendation letters and difficulties in data management. To address these issues, it is necessary to develop the